European Union citizens' views on development assistance for developing countries, during the recent migrant crisis in Europe - Alexander Huepers; Henock B. Taddese; Filippos T. Filippidis (BMC, 2018)
Abstract Background Development assistance from governments of high income countries represents the vast majority of international funding for global health. Recent stagnation of this important source of funding may affect attainment of major global health goals. The financial crisis is widely accredited as denting governments' outlay for development aid, as well as citizen's support for aid. Europe has also recently experienced record levels of migration; the so called 'European migration crisis'. This study aims to analyse trends in public attitudes towards development aid in European Union (EU) countries, in the context of the European migrant crisis. Methods Eurobarometer survey data from 2011 (prior to the migrant crisis) and 2015 (at the peak of the crisis) was analysed for 27 EU countries. The outcome variables related to people's levels of support to three statements around the importance of supporting people in developing countries, increasing countries' commitments to aid and willingness to pay extra for products from developing countries. EU Member States were categorised as 'arrival' or 'destination' countries in view of migration routes and numbers of asylum applications per 100,000 population, respectively. Multiple linear regression analysis was performed, adjusting for countries' economic status (gross domestic product per capita). Results In general, support for development aid has increased from 2011 to 2015, but was largely unaffected by migration status when applying the regression model. In 2015, the belief that development assistance is 'very important' was significantly higher in countries where migrants first arrived compared to other EU Member States, with a trend towards this association also apparent in 2011. Conclusions The positive trends in public support for development aid are encouraging in an age where economic hardships at home, as well as the tone of national political discourses and rising right wing populism appear to suggest otherwise.